Pengaruh pijat common cold terhadap gejala dan lama sembuh batuk pilek pada balita - Ni Made Ariska Diah Pratiwi; Heru Subaris Kasjono; Siti Maimunah (Poltekkes Kemenkes Aceh, 2024)
Background: Baby massage performed on babies aged 0-12 months is effective in relieving the pain of cough and cold symptoms, this is in accordance with the theory that baby massage therapy can increase endurance and relieve cough and cold symptoms in babies.Objective: The research aims to determine the effect of Common Cold massage on the symptoms and duration of recovery from coughs and colds in toddlers. Methods: Quasi experimental method (quasi experimental design), with pre test and post test design. The sample for this research consisted of 36 toddlers. The sampling technique uses purposive sampling technique. The research period is from April 2023 to May 2023. The research location is at Community Health Center One Negara. Data were collected using observation sheets with data analysis techniques using univariate (descriptive) and bivariate (Wilcoxon test) at 95% CI.Results: The average value before treatment was 3,08, including the severe category, while after treatment the average value was 2,00 including the moderate category. The research results obtained (p= 0,000), so it can be concluded that There is an effect of common cold massage on the symptoms and duration of recovery from coughs and colds in toddlers.Conclusion: There are differences in the effect of common cold massage on the symptoms and duration of recovery from coughs and colds in toddlers. Advice for mothers who have toddlers is to do a common cold massage for the child's cough and cold symptoms and do each movement for 15 minutes.Keywords Common Cold Massage, Long Heal Cold Cough